WATER QUALITY ANALYSIS OF CODE RIVER BASED ON METAL AND NONMETAL PARAMETERS USING HEAVY METAL POLLUTION INDEX - Margaretha Widyastuti; Galih Dwi Jayanto; Muhammad Ridho Irshabdillah (Universitas Negeri Medan, 2021)
Code is one of the rivers influenced by a large number of waste-generating human activities in Yogyakarta, Indonesia. Despite continued discharges of pollution loads from anthropogenic waste, the heavy metal pollution index (HPI)—a water quality index assessing heavy metal ions present in a body of water—remains nationally underutilized. The research was intended to 1) analyze the river water quality based on metal and nonmetal parameters typical of domestic waste, 2) calculate HPI using either and both parameters, and 3) evaluate the resultant water quality status. The water quality data were the products of temporal river monitoring conducted by the Forestry and Environmental Office for Yogyakarta. The heavy metal parameters included Fe, Cu, Cd, Cr, and Pb, while the nonmetal parameters were BOD, COD, TSS, ammonia, oil and grease, and total coliforms. Each parameter value was compared with the water quality standard issued in Governor Regulation No. 20/2008. The results showed that the HPI composite of heavy metal parameters classified the river water quality as excellent (2.52), whereas the one representing nonmetal parameters indicated bad quality (55.04). Nevertheless, based on the HPI composed of all parameters, the quality fell into the category excellent (3.94). Consequently, when all metal and nonmetal parameters are combined into the HPI calculation, the river shows a better water quality status.Keywords: HPI (Heavy Metal Pollution Index) water quality, domestic waste, heavy metal, Yogyakarta